Traces of alum shale in the Finnish Caledonides of the Enontekiö Lapland - Jyrki J Lehtovaara (Geographical Society of Finland, 1986)
The existence of alum shale in the small Finnish sector of the Scandinavian Caledonides has been verified by chemical finds. Enhanced values for V and Mo (1050 and 450 ppm, respectively) together with more common tenors of C and U have been reported. These values could be used to discriminate between the alum shale and common black shale otherwise similar in appearance. The find was made in the only slightly metamorphosed lowermost unit of the Caledonide overthrust plates, the Jerta Nappe. This provides further proof of the only parautochthonous character of this nappe and also of the continuity of the alum shale sedimentary facies along the eastern margin of the Caledonides.